Automated design of flexible linkers. Issue 10 (21st December 2015) - Manion, Charles; Arlitt, Ryan; Campbell, Matthew I.; Tumer, Irem; Stone, Rob; Greaney, P. Alex
Abstract : This paper presents a method for the systematic and automated design of flexible organic linkers for construction of metal organic-frameworks (MOFs) in which flexibility, compliance, or other mechanically exotic properties originate at the linker level rather than from the framework kinematics. Abstract : This paper presents a method for the systematic and automated design of flexible organic linkers for construction of metal organic-frameworks (MOFs) in which flexibility, compliance, or other mechanically exotic properties originate at the linker level rather than from the framework kinematics. Our method couples a graph grammar method for systematically generating linker like molecules with molecular dynamics modeling of linkers' mechanical response. Using this approach we have generated a candidate pool of >59 000 hypothetical linkers. We screen linker candidates according to their mechanical behaviors under large deformation, and extract fragments common to the most performant candidate materials. To demonstrate the general approach to MOF design we apply our system to designing linkers for pressure switching MOFs—MOFs that undergo reversible structural collapse after a stress threshold is exceeded.